Empowering Asian Students Through Artificial Intelligence: A Workshop on Predicting Plant Growth to Support Smart Farming - Nurchim Nurchim; Nurmalitasari Nurmalitasari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The integration of Artificial Intelligence (AI) in agriculture has revolutionized traditional farming practices, enhancing productivity, efficiency, and sustainability. This study highlights a workshop aimed at equipping students with practical AI skills, specifically focusing on linear regression techniques for crop growth prediction. The workshop, involved 55 students from nine Asian countries, fostering cross-cultural collaboration. Participants were introduced to theoretical concepts and engaged in hands-on training, covering data preprocessing, region of interest extraction, and model implementation using Python. The program emphasized the role of AI in addressing agricultural challenges such as resource optimization and food security. The workshop was conducted in five stages: preparation, implementation, evaluation, dissemination, and participant engagement. Pre and post-test evaluations revealed a significant improvement in participants’ AI knowledge, with average scores increasing from 45% to 85%. Practical activities enabled students to connect theoretical knowledge with real-world applications, enhancing their ability to predict crop growth using AI techniques. Dissemination efforts included reports and publications to inspire similar global initiatives. The results demonstrated the workshop's effectiveness in bridging knowledge gaps, fostering sustainable agricultural practices, and preparing a skilled workforce capable of leveraging AI to address future challenges in smart farming.